2020
DOI: 10.1088/2053-1591/abc9f2
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the constrained groove pressing on microstructural, mechanical, and fracture properties of brass sheets

Abstract: Constrained groove pressing (CGP) was used for the production of fine-grained brass sheets in different conditions. The process was conducted up to two cycles on brass sheets at room temperature and then half cycle at the temperature of 200 °C. Optical microscopy (OM), scanning electron microscopy (SEM), microhardness measurement, and plane stress fracture toughness was used to investigate the microstructure, mechanical properties, and fracture behavior. Microhardness measurement showed the capability of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Some researchers also tried to process alloys to improve their mechanical properties through CGP. Khakbaz and Kazeminezhad, 69 Moradpour et al, 60 Shahmirzaloo et al, 2 and Rahul et al 66,67 found enhanced properties of Al-Mn alloy, Al-Mg alloy, brass, and stainless steel materials, respectively. The variation in mechanical properties of many materials under the influence of CGP is shown in Table 2.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Some researchers also tried to process alloys to improve their mechanical properties through CGP. Khakbaz and Kazeminezhad, 69 Moradpour et al, 60 Shahmirzaloo et al, 2 and Rahul et al 66,67 found enhanced properties of Al-Mn alloy, Al-Mg alloy, brass, and stainless steel materials, respectively. The variation in mechanical properties of many materials under the influence of CGP is shown in Table 2.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…1 UFG structure and a large fraction of grain boundaries lead to attractive mechanical properties such as higher strength and toughness, longer fatigue life, and better wear resistance. [2][3][4] Wherefore, the potential use of UFG materials is in the aerospace, transportation, medical devices, electronics, and defense industry. 5,6 Analytically, a Hall-Petch law is derived to relate strength and grain size (Equation ( 1)).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ultrafine-grained (UFG) materials have been the subject of extensive research characterized by a polycrystalline structure with grain sizes ranging from submicrometer (100~1000 nm) to nanometer scale (less than 100 nm) [1]. Due to their high fraction of grain boundaries and unique structure, UFG materials exhibit enhanced mechanical properties such as increased strength, toughness, superplasticity, hydrogen storage, fatigue life, radiation resistance, and wear resistance [2][3][4]. Consequently, UFG materials find promising applications in various industries including aerospace, transportation, medical devices, electronics, and defense [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel sheets also can be conveniently processed by groove pressing and nanostructuring can be achieved to promote higher mechanical strength [11]. It is required to carry out groove pressing at worm conditions to deform copper alloys and magnesium alloys to improve the mechanical performance [12,13].…”
Section: Introductionmentioning
confidence: 99%